Effects of Combined Treatment with Acupuncture and Chunggan Formula in a Mouse Model of Parkinson's Disease. (21st November 2019) - Hwang, Tae-Yeon; Song, Min-A; Ahn, Sora; Oh, Ju-Young; Kim, Dong-hee; Liu, Quan Feng; Lee, Wonwoong; Hong, Jongki; Jeon, Songhee; Park, Hi-Joon
Abstract : Parkinson's disease is the second most common neurodegenerative disease. Patients with Parkinson's disease can be treated with a combination of acupuncture and herbal medicine, but studies on the synergistic effects of the combined treatment have not yet been conducted. Thus, we subjected an MPTP-induced Parkinson's disease mouse model to the combined treatment. We used acupoint GB34 for acupuncture and modified Chunggantang (KD5040) as the herbal medicine, as they have been reported to be effective in Parkinson's disease. We investigated the suboptimal dose of KD5040 and then used this dose in the combined treatment. The results showed that the combined treatment had a synergistic effect on improvements in abnormal motor function and neurodegeneration compared with the use of acupuncture or herbal medicine alone. The combined treatment also had a neuroprotective effect via the PI3K/AKT and MAPK/ERK signaling pathways. These findings suggest that the combined treatment with acupuncture and KD5040 can help improve the symptoms of Parkinson's disease.